การหาปริมาณฝุ่นขนาดเล็ก (PM2.5, PM10-2.5, PM10) และความสัมพันธ์ระหว่างปริมาณฝุ่นในบรรยากาศ ภายในอาคารและฝุ่นที่บุคคลได้รับ - สมานชัย เลิศกมลวิทย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
The outside, inside traffic police booth and personal exposure particulate matters: PM10, PM10-25 and PM2.5 in Bangkok sites: Dindaeng, Patumwan, Ramkumhaeng and Ngamwongwan, suburban sites: Talad Ku and Prachasamran and Ayutthaya sites were sampling with personal sampler attached impactor cascade heads and particulate concentrations were measured by gravimetric method using a microbalance. PM10 from co-located operation of the personal sample with beta-attenuation PM10 from PCD showed significantly correlation with r = 0.948, p = 0.004. The 24-hr. average PM10 of Bangkok sites was over 100 micro g/cubic m., (Dindaeng and Ngamwongwan s PM10 were exceeded the National Air Quality standard (120 micro g/cubic m)), while PM2.5 from all sites in Bangkok was exceeded the US EPA standard (65 micro g/cubic m). The inside booth PM10 and PM2.5 was less than outside s. The personal exposure PM10 and PM2.5 was between outside and inside booth concentration. The elemental analysis confirmed that mobile source and road dust was dominant sources in this study. Ratio between PM2.5 and PM10 was considerable vary among sites, the mean PM2.5 to PM10 ratio in Bangkok was 0.74, suburban was 0.65 and Ayutthaya was 0.60, which indicated that PM2.5 was dominated in urban area. The outside, inside booth and personal exposure PM concentration showed significantly correlation to each other (p<0.05). The outside booth PM10 was the most suitable predictor in estimating the inside booth and personal exposure PM10 and PM2.5 concentration.